Method for carbonizing cement-based material through cooperation of foam and CO2

By introducing foaming agents in CO2 carbonized cement base materials to increase the contact area of ​​CO2 and cement base materials, the problem of low use rate of CO2 in the existing technology and uneven product nature of the existing technology have realized the uniform carbonization and performance of cement base materials and performance promote.

CN119371148APending Publication Date: 2025-01-28INST OF ROCK & SOIL MECHANICS CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411483749.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the existing CO2 carbonization technology, the CO2 utilization rate is low and the product properties are uneven, resulting in the carbonization reaction being limited to the surface of the material, lacking controllability, and it is difficult to meet the requirements of industrial applications.

Method used

By introducing the foam agent, the physical characteristics of the CO2 foam are adjusted, the contact area of ​​the cement base material and the CO2 is increased, the carbonized cement base material of the CO2 foam fluid is achieved, and the CO2 is uniformly carbonized inside and outside the material.

Benefits of technology

The use of CO2 is improved, the uniform carbonization of cement base materials has been realized, the mechanical properties and durability of the material are improved, and they have better controllable control. They are suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005098185230000011
    Figure HDA0005098185230000011
  • Figure HDA0005098185230000012
    Figure HDA0005098185230000012
  • Figure HDA0005098185230000021
    Figure HDA0005098185230000021
Patent Text Reader

Abstract

The invention discloses a method for carbonizing a cement-based material through cooperation of foam and CO2, according to the method, CO2 foam fluid prepared from CO2 and a foaming agent solution is used for carbonizing the cement-based material, after the foam and CO2 are transported into internal pores of the cement-based material, the foam decays to enable the CO2 and the cement-based material to be subjected to a carbonization reaction, and simultaneous uniform carbonization of the interior and the exterior of the cement-based material is achieved. According to the invention, the utilization rate of CO2 can be improved, on one hand, the specially designed foaming agent is introduced to obviously increase the contact area between gas (CO2) and solid (cement-based material), and the mode of increasing the contact area can ensure that CO2 fully participates in the carbonization reaction process, so that the utilization rate of CO2 is improved; on the other hand, as CO2 fully participates in the reaction, the emission of unreacted carbon dioxide is reduced, and the conversion efficiency of the carbonization reaction is improved, so that a more remarkable effect is achieved in the whole emission reduction target practice.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to CO 2 The technical field of carbonization-modified cement-based materials is particularly related to a foam-synergistic CO 2 Methods for carbonizing cement-based materials. Background Art

[0002] As global climate change intensifies, greenhouse gas emission reduction has become an important goal for governments and the scientific community. 2 Considered one of the main greenhouse gases, excess CO 2 Emissions have a serious impact on the environment. Therefore, it is necessary to find effective CO 2 Emission reduction and utilization technologies are particularly important. The carbonization process reacts carbon dioxide with raw materials to form stable carbonization products, thus achieving CO 2 capture and utilization.

[0003] Carbonization technology is an innovative method that can effectively utilize construction waste and other solid waste from various sources as raw materials and also as solid materials. This conversion process not only greatly reduces the burden of solid waste on the environment, but also helps to explore new ways and solutions for the recycling of resources. Through this technology, not only can the cost of waste treatment be reduced, but also a virtuous cycle between environmental protection and resource reuse can be promoted.

[0004] In addition, in the process of carbonization of cement-based materials, carbonization technology has shown its unique advantages and significant potential. By implementing the carbonization process, the mechanical properties, durability and impermeability of cement-based materials can be significantly improved. The calcium carbonate generated in this process can strengthen the structure of cement-based materials at the microscopic level, further improving their strength and stability.

[0005] Currently, CO 2 Carbonization technology is a hot topic in the research of modifying cement-based materials to improve their physical and chemical properties. However, the existing carbonization methods may have the following two problems: 1. 2 Low utilization rate: In many carbonization processes, CO 2 1. Failure to participate as an effective reactant leads to limited emission reduction effect; 2. Uneven product properties: The products of existing carbonization methods often have uneven structures and properties. The carbonization reaction may only occur on the surface of the material. The calcium carbonate precipitation formed by surface carbonization hinders the CO 2 Migration into the interior of the material limits the carbonization inside the material, lacks controllability, and is difficult to meet the requirements of industrial applications. Summary of the invention

[0006] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a foam synergistic CO 2 The method for carbonizing cement-based materials can adjust CO by introducing a foaming agent. 2 The physical properties of the foam change the carbonization of cement-based materials and CO 2 The contact mode improves the carbonization modification of cement-based materials with CO 2 The contact area can realize the microstructure control of cement-based materials and further improve the performance of cement-based materials.

[0007] The technical solution adopted to achieve the above-mentioned purpose of the present invention is:

[0008] A foam synergistic CO 2 Method for carbonizing cement-based materials using CO 2 Mixed fluid with foaming agent solution or CO 2 CO prepared with blowing agent solution 2 Foam fluid carbonization cement-based materials, foam synergistic CO 2 After migrating to the pores inside the cement-based material, the foam decays and CO 2 Carbonization reaction occurs with cement-based materials to achieve uniform carbonization inside and outside of the cement-based materials at the same time.

[0009] Furthermore, the CO 2 The preparation method of the foam fluid is as follows:

[0010] 1. Evenly mix the foaming agent and distilled water to obtain a foaming agent solution;

[0011] 2. Mix the foaming agent solution with CO 2 Gas mixing, when the pressure of the mixed system reaches 3-5MPa, the foaming agent solution and CO 2 The gas mixture is stirred at high speed, and after the stirring is completed, CO is obtained. 2 Foamy fluid.

[0012] Furthermore, the foaming agent is alkyl polysaccharide.

[0013] Furthermore, the mass fraction of the foaming agent solution is 0.01-1wt%.

[0014] Furthermore, the stirring speed during the high-speed stirring is 2000-3000 rpm.

[0015] Further, the carbonization method of the cement-based material is:

[0016] If the cement-based material is in columnar shape, load the cement-based material into a vacuum-treated carbonization reactor and inject CO into the injection end of the carbonization reactor. 2 Foam fluid or CO2 The mixed fluid with the foaming agent solution is used to maintain the pressure in the injection end of the carbonization reactor at 0.5-1.5MPa, and the CO 2 The foam fluid enters from one end of the cement-based material, flows through the inside of the cement-based material and flows out from the other end of the cement-based material. When the liquid flows out from the other end of the cement-based material, the carbonization reactor is sealed and the injection of CO into the carbonization reactor is stopped. 2 The foam fluid is then heated to 30-60°C in the reactor and carbonized at 30-60°C for 24-36 hours. After the carbonization is completed, the cement-based material is taken out and dried to obtain CO 2 Carbonation-modified cement-based materials;

[0017] If the cement-based material is in granular form, place the cement-based material in a vacuum-treated carbonization reactor and inject CO into the carbonization reactor. 2 Foam fluid or CO 2 When the pressure in the carbonization reactor reaches 0.5-1.5 MPa, the carbonization reactor is sealed and the injection of CO into the carbonization reactor is stopped. 2 The foam fluid is then heated to 30-60°C in the reactor and carbonized at 30-60°C for 24-36 hours. After the carbonization is completed, the cement-based material is taken out and dried to obtain CO 2 Carbonation-modified cement-based materials.

[0018] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0019] 1. The present invention can improve CO 2 On the one hand, the present invention introduces a specially designed foaming agent to significantly increase the gas (CO 2 ) and the solid (cement-based material). This increased contact area ensures that CO 2 Fully participate in the carbonization reaction process to improve the utilization rate of carbon dioxide; on the other hand, due to the 2 It is able to fully participate in the reaction, reducing the emission of unreacted carbon dioxide and improving the conversion efficiency of the carbonization reaction, thereby playing a more significant role in the practice of the overall emission reduction target.

[0020] 2. The present invention uses a foam system to utilize foam to synergize CO 2 Migrate to the internal pores of cement-based materials, and the foam decays to make CO 2 It reacts with cement-based materials to achieve simultaneous carbonization inside and outside of the cement-based materials, thereby achieving uniform carbonization of the cement-based materials, solving the shortcoming in the prior art that only the surface of cement-based materials can be carbonized, and providing a more uniform microstructure for the modified cement-based materials, thereby improving their overall performance.

[0021] 3. The present invention can more accurately adjust the reaction conditions (such as temperature, pressure and foam characteristics) by introducing a foaming agent, making the reaction process more controllable. This controllability helps to ensure uniform carbonization inside and on the surface of the modified cement-based material.

[0022] 4. The present invention utilizes CO efficiently 2 It not only improves the utilization efficiency of waste concrete resources, but also provides more effective technical means for achieving emission reduction goals, and plays a positive role in environmental protection and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The foam of Example 1 cooperates with CO 2 Schematic diagram of the structure of the device for carbonizing cement-based materials.

[0024] Figure 2 This is a comparison chart of the carbonization effects of bidirectional carbonization and unidirectional carbonization on cement cylindrical samples.

[0025] Figure 3 The foam of Example 3 synergizes CO 2 Schematic diagram of the structure of the device for carbonizing cement-based materials.

[0026] Figure 4 This is a diagram showing the changes in pressure inside the carbonization reactor during the carbonization process of recycled aggregate particles.

[0027] Figure 5 For different ratios of CO 2 Comparison of the carbonization effect of foam fluid on recycled aggregate particles

[0028] Among them, 1-carbon dioxide cylinder, 2-gas booster pump, 3-water source container, 4-high-pressure injection pump, 5-granular sample carbonization reactor, 6-six-way valve one, 7-pressure sensor one, 8-vacuum pump, 9-confining pressure pump, 10-column sample carbonization reactor, 11-cylindrical cement sample, 12-pressure gauge, 13-six-way valve two, 14-pressure sensor two, 15-data collector, 16-monitoring computer, 17-back pressure valve, 18-collection container, 19-nitrogen cylinder, 20-high-pressure resistant high-speed agitator, 21-stirring speed regulator, 22-temperature controller, 23-pressure sensor three, 24-pressure sensor four. DETAILED DESCRIPTION

[0029] In order to facilitate those skilled in the art to understand and implement the present invention, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the implementation examples described herein are only used to illustrate and explain the present invention and are not used to limit the present invention.

[0030] The foam synergistic CO of the present invention is described below in conjunction with the accompanying drawings. 2A device for carbonizing cement-based materials is described in detail.

[0031] Example 1

[0032] The foam provided in this embodiment cooperates with CO 2 The device structure of carbonized cement-based materials is as follows Figure 1 As shown, the overall device includes three units: a mixing unit, a carbonization reaction unit, and a pressure monitoring unit.

[0033] The mixing and preparation unit includes a gas injection module, a liquid injection module and a six-way valve. 2 Gas cylinder 1, gas booster pump 2, CO 2 The gas cylinder 1 and the gas booster pump 2 are connected through a pipe 1. The liquid injection module includes a water source container 3, a high-pressure liquid injection pump 4, and a piston container 5 containing a foaming agent solution. The water source container 3, the high-pressure liquid injection pump 4, and the piston container 5 are connected through a pipe 2. The high-pressure liquid injection pump 4 pumps water from the water source container 3 into the lower part of the piston container 5, pressurizes the piston container 5, and thus delivers the foaming agent solution on the upper part of the piston container 5 into the six-way valve 1 6. Pipe 1 and pipeline 2 are respectively connected to the two branch interfaces of the six-way valve 1 6. The CO pumped by the gas injection module 2 The foaming agent aqueous solution pumped by the injection module merges at the six-way valve 6 to form CO 2 In addition, the six-way valve 6 is equipped with a pressure sensor 7, which communicates with the monitoring computer 16 through the data collector 15 to monitor the pressure of the fluid injected into the front end of the columnar sample carbonization reactor 10.

[0034] The carbonization reaction unit includes a vacuum pump 8, a confining pressure pump 9, a columnar sample carbonization reactor 10, a cylindrical cement sample 11, a six-way valve 13, a back pressure valve 17 and a nitrogen bottle 19. The columnar sample carbonization reactor 10 is composed of a pressure-resistant steel barrel, a CO2-resistant steel barrel, a 2 Before the carbonization reaction experiment is carried out, the air inside the columnar sample carbonization reactor 10 and the cylindrical cement sample 11 is extracted by the vacuum pump 8 to maintain the CO 2 In order to allow the mixed fluid to enter the cylindrical cement sample 11, the confining pressure pump 9 is used to pump the mixed fluid into the pressure-resistant steel barrel and the CO2-resistant 2Water is injected into the annular space formed by the rubber sleeve to increase the confining pressure of the rubber sleeve on the cylindrical cement sample 11, thereby inhibiting the mixed fluid from flowing along the side of the cylindrical cement sample, and the confining pressure is monitored by a pressure gauge 12. The tail end of the columnar sample carbonization reactor 10 is connected to the six-way valve 2 13, and the six-way valve 2 13 is equipped with a pressure sensor 2 14, which also communicates with the monitoring computer 16 through the data collector 15 to monitor the tail pressure of the columnar sample carbonization reactor 10. The back pressure valve 17 is connected to the six-way valve 2 13, and the back pressure valve 17 is used to adjust the internal pressure of the columnar sample carbonization reactor 10, and the nitrogen bottle 19 is used to control the back pressure of the back pressure valve. In addition, the outlet of the back pressure valve 17 is connected to the collection container 18 for collecting the fluid flowing out of the columnar sample carbonization reactor 10.

[0035] The pressure monitoring unit includes a pressure sensor 1 7, a pressure sensor 2 14, a data collector 15 and a monitoring computer 16. The pressure sensor 1 7 and the pressure sensor 2 14 are connected to the six-way valve 1 6 and the six-way valve 2 13 respectively, and are used to monitor the front end pressure and the tail end pressure of the cylindrical cement sample. The two sensors are connected to the data collector 15, and the current signal of the sensor is converted into pressure data through the data collector 15, and the internal pressure of the columnar sample carbonization reactor 10 is obtained by communicating with the monitoring computer.

[0036] Example 2

[0037] The device of Example 1 is used. This example takes a cylindrical cement sample (referred to as a cement cylindrical sample) as an example to describe the foam synergistic CO 2 Carbonization method, the specific method is as follows:

[0038] 1. Dry the cement cylinder sample 11 and then put it into the CO2-resistant 2 In the rubber sleeve, the outer steel barrel of the columnar sample carbonization reactor 10 and the CO resistant 2 Distilled water is pumped inside the annular space formed by the rubber sleeve, and the confining pressure pump 9 is set to apply a confining pressure to the columnar sample carbonization reactor 10 that is always 3MPa higher than the injection pressure of the mixed fluid (generally 2.5-3.5Mpa);

[0039] 2. Dissolve the alkyl polyglycoside in distilled water to prepare 300 mL of an alkyl polyglycoside aqueous solution with a mass fraction range of 0.15 wt%. After the solution is prepared, transfer the solution to the piston container 5;

[0040] 3. Turn on the vacuum pump 8 to extract the internal air of the columnar sample carbonization reactor 10 and the cement cylinder sample. The vacuuming time is at least 12 hours;

[0041] 4. Use the back pressure valve 17 to control the output pressure of the nitrogen cylinder 19 to be 1 MPa (that is, the back pressure of the back pressure valve is 1 MPa).

[0042] 5. After the thermostat temperature reaches the target temperature, turn on the CO 2 The gas cylinder 1 and the high-pressure liquid injection pump 4 are used to inject the mixed fluid into the cylindrical cement sample 11, and the CO is controlled by the gas booster pump 2 and the high-pressure liquid injection pump 4 respectively. 2 and the flow rate of the foaming agent aqueous solution. At the same time, the pressure monitoring software of the monitoring computer 16 is turned on to record the pressure changes of the pressure sensor 1 7 and the pressure sensor 2 14. In this embodiment, the control CO 2 When the tail end of the cylindrical cement sample 11 is discharged and the pressure difference between the front and rear ends of the columnar sample carbonization reactor 10 (the pressure difference is generally 0.5-1.5Mpa) reaches equilibrium, close the valves at the front and rear ends of the columnar sample carbonization reactor 10, and stop injecting CO immediately. 2 A mixed fluid formed by mixing with a foaming agent solution.

[0043] 8. Place the columnar sample carbonization reactor 10 in a constant temperature box, use the constant temperature box to heat the columnar sample carbonization reactor to 10 to 40°C and maintain it for 24 hours. After the carbonization is completed, take out the cement-based material and dry it to obtain CO 2 Carbonated modified cement cylindrical sample A (referred to as carbonized cement cylindrical sample A);

[0044] 9. Cut the carbonized cement cylinder sample A into 4 slices with a thickness of 1 cm, and calculate the CO absorption of each slice by thermogravimetric analysis. 2 The absorption of CO is measured by taking the distance between the carbonization start end of the carbonized cement cylinder and the middle of each slice as the horizontal axis and the absorption of CO by each slice as the horizontal axis. 2 The absorption amount is plotted as the vertical coordinate to obtain the unidirectional carbonization curve of the carbonized cement cylindrical sample A.

[0045] 10. Take another cement cylindrical sample and repeat steps 1-8 to obtain carbonated cement cylindrical sample B.

[0046] 11. Reverse the direction of the carbonized cement cylindrical sample B obtained in step 9 and re-carbonize it according to the above-mentioned carbonization method to obtain the carbonized cement cylindrical sample C.

[0047] 12. The carbonized cement cylindrical sample C is processed and analyzed according to the method of step 9 to obtain the bidirectional carbonization curve of the carbonized cement cylindrical sample C, the unidirectional carbonization curve of the carbonized cement cylindrical sample A and the bidirectional carbonization curve of the carbonized cement cylindrical sample C as shown in FIG. Figure 2 As shown by Figure 2 It can be seen that after bidirectional carbonization, the carbonized cement cylinder has a 2 The carbonization effect is better and more uniform. After unidirectional carbonization, the carbonized cement cylinder has a better absorption of CO2 The absorption is relatively less, the carbonization effect is worse, and the carbonization is uneven.

[0048] Example 3

[0049] The foam provided in this embodiment cooperates with CO 2 The structure of the device for carbonizing cement-based materials is as follows Figure 2 As shown, including CO 2 There are three units in total, including foam fluid preparation unit, carbonization reaction unit and pressure monitoring unit.

[0050] CO 2 The foam fluid preparation unit consists of CO 2 The gas cylinder 1, the gas booster pump 2, the high-speed high-pressure stirrer 20 and the stirring speed regulator 21 are composed. 2 Before the foam fluid is produced, a certain volume of foaming agent solution is filled into the high-pressure high-speed stirrer 20, and the vacuum pump 8 is turned on to extract the air inside the high-pressure high-speed stirrer 20 and the granular sample carbonization reactor 5. After the vacuum operation is completed, CO is filled into the high-pressure high-speed stirrer 20 through the gas booster pump 2. 2 The stirring speed of the stirring rod of the high-speed high-pressure stirrer 20 is regulated by the stirring speed regulator 21 to form CO 2 A pressure sensor 24 is installed on the top of the high-speed high-pressure agitator 20 to monitor the injection of CO 2 After that, it can withstand the pressure in the high-pressure high-speed agitator 20.

[0051] The carbonization reaction unit includes a granular sample carbonization reactor 5 (with a self-heating function), a temperature controller 22 and a vacuum pump 8. Before the experiment, a certain amount of aggregate particles is added to the granular sample carbonization reactor 5, and the target temperature inside the granular sample carbonization reactor 5 is set by the temperature controller 22. Subsequently, the bottom valve of the high-speed high-pressure stirrer 20 is opened to add the prepared high-pressure CO 2 The foam fluid is introduced into the granular sample carbonization reactor 5 .

[0052] The pressure monitoring unit is composed of a pressure sensor 3 23, a pressure sensor 4 24, a data collector 15 and a monitoring computer 16. The pressure sensor 8 is installed on the top of the granular sample carbonization reactor 5, and establishes communication with the monitoring computer 16 through the data collector 15. The current signal of the pressure sensor 3 23 is converted into pressure data through the data collector 15, which is used to monitor the pressure change during the carbonization reaction.

[0053] Example 4

[0054] The device of Example 3 is used. This example takes recycled aggregate particles as an example to describe the foam synergistic effect of CO 2Carbonization method, the specific method is as follows:

[0055] 1. Dissolve the alkyl polyglycoside in distilled water to prepare 300 mL of an alkyl polyglycoside aqueous solution with a mass fraction of 0.01 wt %; then transfer the prepared alkyl polyglycoside solution to a high-pressure resistant high-speed stirring container 20;

[0056] 2. Weigh 100.0 g of dried recycled aggregate particles using a precision electronic balance and transfer them to the granular sample carbonization reactor 5. Turn on the vacuum pump 8 to extract the internal air of the high-pressure high-speed stirring container 20 and the carbonization reaction container 5 to eliminate the interference of impurity gases on the experiment. The vacuuming time is 12 hours.

[0057] 3. Set the temperature of the temperature controller 22 to 40° C., turn on the heating component (such as a heating jacket) of the granular sample carbonization reactor 5, and heat the recycled aggregate particles inside the granular sample carbonization reactor 5;

[0058] 4. Turn on CO 2 The gas cylinder 1, the gas booster pump 2 and the valve at the top of the high-pressure resistant high-speed stirring container 20 are connected to the gas cylinder 1, the gas booster pump 2 and the valve at the top of the high-pressure resistant high-speed stirring container 20. 2 When the internal pressure of the high-pressure high-speed stirring container 20 reaches 5 MPa, the CO 2 Valves on the top of the gas cylinder 1, gas booster pump 2 and high-pressure resistant high-speed stirring container 3;

[0059] 5. Turn on the stirring speed regulator 21 and adjust the stirring speed of the high-pressure resistant high-speed stirring container 3 to 3000 rpm. 2 The alkyl polysaccharide solution is stirred to generate foam, and the stirring time is 300s. After the stirring time is reached, the stirring speed regulator 21 is turned off, and the stirring is stopped to obtain CO 2 Foamy fluid;

[0060] 6. Open the bottom valve of the high-pressure high-speed stirring container 20 and the top valve of the granular sample carbonization reactor 5. Under the action of the internal high pressure, the CO 2 The foam fluid will be pressed into the granular sample carbonization reactor 5. At the same time, the pressure monitoring software in the monitoring computer 16 is turned on to monitor the internal pressure in the granular sample carbonization reactor 5. When the internal pressure in the granular sample carbonization reactor 5 reaches 1 MPa, the top valve of the granular sample carbonization reactor 5 is closed to stop the injection of high-pressure CO. 2 Foamy fluid.

[0061] 8. Keep the granular sample carbonization reactor 5 at 40°C for 24 hours. During the carbonization, the pressure change in the reactor body is monitored in real time through the pressure sensor 3 23. After the carbonization is completed, the recycled aggregate particles are taken out and dried to obtain CO 2 The carbonized recycled aggregate particles (referred to as carbonized recycled aggregate particles) are carbonized and the carbon fixation amount of the carbonized recycled aggregate particles is measured by thermogravimetric analysis.

[0062] During the carbonization process, the pressure in the granular sample carbonization reactor 5 changes with the carbonization time as shown in Figure 4 As shown by Figure 4 It can be seen that as the carbonization progresses, the pressure in the granular sample carbonization reactor 5 gradually decreases, which shows that CO 2 Gas is continuously consumed during the carbonization process.

[0063] 9. Repeat steps 1-8, except that in step 2, prepare an aqueous solution of alkyl polysaccharide with a mass fraction of 0.1 wt%;

[0064] 10. Repeat steps 1-8, except that in step 2, prepare an aqueous solution of alkyl polysaccharide with a mass fraction of 1 wt%.

[0065] CO prepared from aqueous solutions of alkyl polysaccharides with different concentrations 2 The foam fluid carbonizes the recycled aggregate particles, and the recycled aggregate particles react with CO 2 The absorption amount of Figure 5 As shown by Figure 5 It can be seen that the higher the concentration of the alkyl polysaccharide aqueous solution, the easier it is to prepare CO 2 The foam fluid carbonizes the recycled aggregate particles, and the higher the amount of carbon dioxide absorbed by the recycled aggregate particles.

Claims

1. A method for carbonizing cement-based materials by using foam in conjunction with CO2, characterized in that: The cement-based material is carbonized using a mixed fluid of CO2 and a foaming agent solution or a CO2 foam fluid prepared from a CO2 and a foaming agent solution. After the foam cooperates with the CO2 to migrate into the internal pores of the cement-based material, the foam decays to cause a carbonization reaction between the CO2 and the cement-based material, thereby achieving simultaneous and uniform carbonization of the inside and outside of the cement-based material.

2. The method for carbonizing cement-based materials with foam and CO2 according to claim 1, characterized in that The preparation method of the CO2 foam fluid is as follows: 2.

1. Mix the foaming agent and distilled water evenly to obtain a foaming agent solution; 2.

2. Mix the foaming agent solution with CO2 gas. When the pressure of the mixed system reaches 3-5 MPa stably, stir the mixture of the foaming agent solution and CO2 gas at a high speed. After the stirring is completed, a CO2 foam fluid is obtained.

3. The method for carbonizing cement-based materials with foam and CO2 according to claim 2, characterized in that: The foaming agent is alkyl polysaccharide.

4. The method for carbonizing cement-based materials with foam and CO2 according to claim 2, characterized in that: The mass fraction of the foaming agent solution is 0.01-1wt%.

5. The method for carbonizing cement-based materials with foam and CO2 according to claim 2, characterized in that: The stirring speed during the high-speed stirring is 2000-3000 rpm.

6. The method for carbonizing cement-based materials with foam and CO2 according to claim 2, characterized in that The carbonization method of the cement-based material is: If the cement-based material is in a columnar shape, the cement-based material is loaded into a carbonization reactor that has been vacuumed, and a CO2 foam fluid or a mixed fluid of CO2 and a foaming agent solution is injected into the injection end of the carbonization reactor to maintain the pressure in the injection end of the carbonization reactor at 1.5-2.5 MPa. The CO2 foam fluid is allowed to enter from one end of the cement-based material by a displacement method, flow through the inside of the cement-based material, and flow out from the other end of the cement-based material. When liquid flows out of the other end of the cement-based material, the carbonization reactor is sealed and the injection of the CO2 foam fluid into the carbonization reactor is stopped. The reactor is then heated to 30-60° C. and carbonized at 30-60° C. for 24-36 hours. After the carbonization is completed, the cement-based material is taken out and dried to obtain a CO2 carbonization-modified cement-based material. If the cement-based material is in granular form, the cement-based material is placed in a vacuum carbonization reactor, and CO2 foam fluid or a mixed fluid of CO2 and foaming agent solution is injected into the carbonization reactor. When the pressure in the carbonization reactor reaches 0.5-1.5MPa, the carbonization reactor is sealed and the injection of CO2 foam fluid into the carbonization reactor is stopped. The reactor is then heated to 30-60°C and carbonized at 30-60°C for 24-36h. After the carbonization is completed, the cement-based material is taken out and dried to obtain the CO2 carbonization-modified cement-based material.

Citation Information

Cited By

  • Preparation method of carbon sequestration building material through carbon dioxide foaming storage and low-pressure forming

    CN120794687A